History without evidence: Latin American inequality since 1491 - Jeffrey G. Williamson (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2009)
Most analysts of the modern Latin American economy hold to a pessimistic belief in historical persistence - they believe that Latin America has always had very high levels of inequality, suggesting it will be hard for modern social policy to create a more egalitarian society. This paper argues that this conclusion is not supported by what little evidence we have. The persistence view is based on an historical literature which has made little or no effort to be comparative. Modern analysts see a more unequal Latin America compared with Asia and the rich post-industrial nations and then assume that this must always have been true. Indeed, some have argued that high inequality appeared very early in the post-conquest Americas, and that this fact supported rent-seeking and anti-growth institutions which help explain the disappointing growth performance we observe there even today. This paper argues to the contrary. Compared with the rest of the world, inequality was not high in pre-conquest 1491, nor was it high in the postconquest decades following 1492. Indeed, it was not even high in the mid-19th century just prior Latin America's belle époque. It only became high thereafter. Historical persistence in Latin American inequality is a myth.
Keywords: N16; N36; O15; D3; 330; Inequality; development; Latin America